Analysis of ESG’s impact on the environment based on the financial assessment perspective - Zhang, Guanxiao (Transactions on Economics, Business and Management Research, 2024)
In recent years, financial performance evaluation has been regarded as one of the methods to measure a company’s achievement of its performance goals, but its effectiveness has always been questioned. This has prompted people to hope to use ESG as a better indicator to replace financial performance. This article uses a dual weight evaluation model to demonstrate the impact of ESG on the environment. Secondly, this article establishes an environmental model, forms the Environmental Index (CI), and studies its changes. The results showed that adopting ESG can significantly reduce the rate of environmental degradation, indicating that it can be an important tool to help achieve sustainable development.